Doxorubicin aqueous systems at low concentrations: Interconnection between self-organization, fluorescent and physicochemical properties, and action on hydrobionts - Ryzhkina, Irina; Murtazina, Lyaisan; Kostina, Larisa; Dokuchaeva, Irina; Sergeeva, Svetlana; Meleshenko, Kristina; Shevelev, Maxim; Petrov, Andrew (Frontiers in Chemistry, 2022)
Doxorubicin (Dox) is a highly effective cytostatic antibiotic that exhibits activity against a wide range of malignant neoplasms and is often used as the basis of various anti-tumor compositions. However, the use of Dox in therapeutic doses is associated with high systemic toxicity, which makes it urgent to find ways to reduce therapeutic concentrations, which is necessary primarily to minimize the side effects on the patient’s body, as well as to reduce the harmful effects on aquatic ecosystems, commonly polluted by toxic pharmaceuticals. Studying the self-organization, physicochemical and spectral patterns, and their relation to bioeffects of Dox solutions in the range of low concentrations can reveal useful insights into the unknown effects of Dox as a cytostatic and potential pollutant of ecosystems. The self-organization in solutions and on substrates, physicochemical and spectral properties, and action of Dox solutions on hydrobionts were studied in the range of calculated concentrations from 1·10−20 to 1·10−4 M by methods of dynamic and electrophoretic light scattering (DLS and ELS), scanning electron microscopy (SEM), scanning probe microscopy (SPM), fluorescence spectroscopy, UV absorption spectroscopy, conductometry, tensiometry, pH-metry. Certified techniques for monitoring the toxicity of natural water and wastewater were used to establish the interconnection between these phenomena. It was shown that aqueous solutions of Dox are dispersed systems which rearrange their dispersed phase measuring hundreds of nm in size (nanoassociates) at dilution, followed by concerted changes in nanoassociates’ parameters (size and ζ-potential) and properties of systems, as well as their bioassay results. SPM and SEM results confirm and complement the DLS and ELS data indicating the existence of nanoassociates in dilute Dox solutions.